ANALISIS PENERAPAN METODE DISKUSI KELOMPOK PADA MATA PELAJARAN EKONOMI UNTUK MENINGKATKAN KETERLIBATAN BELAJAR SISWA - Amelia Simorangkir; Gissela Afriani Putri; Nadila Eka Lestari; Pradilan Sandi; Carla Fitri Ramadhani; Muhammad Hidayat; Muhammad Rizki; Defrizal; Hewi Irhamna; M. Dirga Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the application of the group discussion method in economics subjects and its contribution to student learning engagement at the senior high school level. A qualitative descriptive approach with a case study design was employed, with data collected through participatory observation, in-depth interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña. The findings reveal that group discussion is implemented through five stages: group formation, topic presentation, discussion, result presentation, and reflection. This method enhances student learning engagement across three dimensions: behavioral, emotional, and cognitive. The teacher's role as an active facilitator is the key determining factor. Supporting factors include teacher competence and a conducive classroom climate, while inhibiting factors include student dominance and limited time allocation. Findings are analyzed through Constructivism, Social Learning Theory, Student Engagement Theory, Cooperative Learning Theory, and Active Learning Theory.